Psychological status of general population 1 year after the outbreak of COVID-19: a cross-sectional study based on SCL-90 - Chen, Xia; Hu, Yue; Deng, Yuan; Wang, Xin; Yang, Xiao; Wang, Ying; Lian, Yanli; Wang, Shiping; Xiang, Xinju; Liu, Chan; Wu, Fang; Chen, Shaochuan; et al. (Frontiers in Psychology, 2024)
Introduction The mental health of populations is usually affected after a disaster event. However, it is not known what the level of mental health of Chinese population 1 year after COVID-19, nor what factors influence it. Aim This study aimed to examine the mental health status of general population in Chengdu 1 year after COVID-19, and then analyse influencing factors. Method This study is a cross-sectional survey based on the SCL-90 questionnaire. Continuous data were described as M and SD, and counting data were described as frequencies(n) and percentages (%). Chi-square test or Fisher’s exact test were used for statistical inference, and significance variables were included in the binary logistic regression equation for multivariate analysis. Results There were 172 participants with positive screening results. Age, marital status, number of kids, self-perceived health and the presence of chronic disease had an effect on screening results. Logistic regression analysis showed that age and self-perceived health were the main influencing factors. Discussion Young people aged 18–19 and those who consider themselves not very healthy were at higher risk of poor mental health 1 year after the COVID-19 outbreak. Impact statement Community institutions and community workers should focus on the mental health status of people 1 year after COVID-19, with a focus on people with poor self-perceived health and younger age groups, and take early preventive measures.